Effectiveness of biologic therapies in achieving treatment targets in inflammatory bowel disease; real-world data from the Middle East (ENROLL study) - Shehab, Mohammad; Alfadhli, Ahmad; Abdullah, Israa; Alostad, Wrood; Marei, Alaa; Alrashed, Fatema (Frontiers in Pharmacology, 2024)
Background Real-world data assessing the effectiveness of biologics in patients with inflammatory bowel disease (IBD) in the Middle East are not well-established. In our study, we evaluated the effectiveness of biologic therapies in achieving clinical and endoscopic outcomes in biologic naïve patients with IBD. Design A retrospective chart review was conducted at two tertiary care gastroenterology centers, using electronic medical records of patients with moderate to severe IBD. The study period was from October 2017 to October 2023. Patients who were on infliximab, adalimumab, ustekinumab, or vedolizumab for a duration of 12 months were included in the analysis. The primary outcomes were the percentage of IBD-related hospitalizations or surgeries, achieving steroid-free remission, and endoscopic remission. Results A total of 422 patients were included in the study, of which, 264 (62.5%) patients had Crohn’s disease (CD) and 158 (39%) with ulcerative colitis (UC). In patients with CD, endoscopic remission was attained in 51 (52%) of the patients on adalimumab, 38 (53%) of the patients on infliximab, 34 (56%) of the patients on ustekinumab and 16 (51%) patients on vedolizumab. In patients with UC, endoscopic remission was attained in 40 (56%) of the patients on infliximab, 26 (61%) of the patients on adalimumab, 8 (55%) of the patients on ustekinumab and 11 (53%) patients on vedolizumab. Conclusion Adalimumab, infliximab, and ustekinumab and vedolizumab were all effective in achieving clinical and endoscopic clinical outcomes in IBD, in both UC and CD. The findings of this study suggest that the efficacy of biologics in the Middle East is similar to that in the western population.